2010
DOI: 10.1021/es102659p
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prochloraz or Propylthiouracil on the Cross-Talk between the HPG, HPA, and HPT Axes in Zebrafish

Abstract: The objective of this study was to assess chemical-induced effects on cross-talk among the hypothalamic-pituitary-gonad (HPG), hypothalamic-pituitary-adrenal (HPA), and hypothalamic-pituitary-thyroid (HPT) axes of fish. Adult female zebrafish were exposed to 300 µg/L prochloraz (PCZ) or 100 mg/L propylthiouracil (PTU), and the transcriptional profiles of the HPG, HPA, and HPT axes were examined. Exposure to PCZ decreased plasma testosterone (T) and 17 -estradiol (E2) concentrations and affected HPA and HPT axe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(50 citation statements)
references
References 39 publications
6
39
3
2
Order By: Relevance
“…For example, a study showed the antiestrogenic/antiandrogenic activity of PCP in cultured Xenopus oocytes and inhibition of ovarian steroidogenesis, accompanied by decreased production of both progesterone and T (Orton et al, 2009). Furthermore, there is accumulating evidence of cross-talk between the thyroid and estrogen signaling pathways, and the impact of xenohormones cannot be assessed exploring only a single pathway (Ghisari and Bonefeld-Jorgensen, 2005;Liu et al, 2011). Hence, in vitro tests and further in vivo studies will be needed to investigate the impact of endocrine disruptors on certain endocrine systems at the whole-organism level.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study showed the antiestrogenic/antiandrogenic activity of PCP in cultured Xenopus oocytes and inhibition of ovarian steroidogenesis, accompanied by decreased production of both progesterone and T (Orton et al, 2009). Furthermore, there is accumulating evidence of cross-talk between the thyroid and estrogen signaling pathways, and the impact of xenohormones cannot be assessed exploring only a single pathway (Ghisari and Bonefeld-Jorgensen, 2005;Liu et al, 2011). Hence, in vitro tests and further in vivo studies will be needed to investigate the impact of endocrine disruptors on certain endocrine systems at the whole-organism level.…”
Section: Discussionmentioning
confidence: 99%
“…Logically, up-regulations of NIS and TG may lead to the increase of THs production, whereas decreased T4 and T3 levels were observed in this study. Previously, it has been reported that model chemicals, 6-N-propylthiouracil (PTU), which is an inhibitor of TH synthesis-related enzymes, and perfluorooctanoic acid (PFOA) could decrease concentrations of T4 and T3 in the zebrafish and up-regulate gene expressions in the HPT axis (Liu et al, 2011;Yu et al, 2011). The authors suggested that up-regulations of gene expression might be a compensatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, the endocrine system is very complex and affected by many factors, and previous studies have shown that liver damage may not only induce sex hormone changes [127], but also reduce hepatic thyroxine deiodination in animals [137], which in turn causes a decline in peripheral triiodothyronine production [130]. A previous study demonstrated that chemical-caused effects on one endocrine axis pathway will also indirectly affect the other endocrine axes in zebrafish [138]. Recently, it has been found that cholesterol, the precursor of all classes of steroid hormones, is significantly altered in zebrafish [139] and mice [136] after MCs exposure, suggesting that MCs are capable of disrupting the endocrine system and inducing reproductive toxicity [38,87].…”
Section: Sex Hormones Hpg Axis Liver and Endocrine-disrupting Effectsmentioning
confidence: 99%